A case of hypophysitis after COVID-19 vaccination with a detection of anti-pituitary antibody, with review of literature - Chika Kyo; Tomoko Kobayashi; Shintaro Iwama; Rieko Kosugi; Fumikazu Sawabe; Ryo Hayafusa; Yuki Sakai; Tatsuo Ogawa; Masato Kotani; Tatsuhide Inoue; Hiroshi Arima; Hiroyuki Ariyasu (Endocrine Journal)
COVID-19 vaccines have resulted in a remarkable reduction in both the morbidity and mortality associated with COVID-19. However, there are reports of endocrine rare clinical conditions linked to COVID-19 vaccination. In this report, we present a case of hypophysitis following COVID-19 vaccination and review the literature on this condition. This case involved a 72-year-old male with type 1 diabetes who experienced symptoms such as vomiting, appetite loss, and headaches following his fifth COVID-19 vaccine dose. He was diagnosed with secondary adrenal insufficiency; subsequent assessment revealed an enlarged pituitary gland. Unlike previous cases, our patient has partial recovery from pituitary insufficiency, and his pituitary function gradually improved over time. Anti-pituitary antibodies (APAs) against corticotrophs, thyrotrophs, gonadotrophs, and folliculo stellate cells (FSCs) were detected in serum samples taken 3 months after onset. Hypophysitis after COVID-19 vaccination is a rare clinical condition, with only eight cases reported by the end of 2023, most occurring after the initial or second vaccination. Symptoms of hypophysitis after COVID-19 vaccination are similar to those of classic pituitary dysfunction. Pituitary insufficiency is persistent, with five of the above eight patients presenting posterior pituitary dysfunction and three patients presenting only anterior pituitary dysfunction. Two of those eight patients had autoimmune diseases. Our case suggests a potential link between acquired immunity, APA production, and pituitary damage. To elucidate the etiology of hypophysitis associated with COVID-19 vaccination, detailed investigation of patients with nonspecific symptoms after vaccination against COVID-19 is necessary.